MEMAHAMI MEDIA PEMBELAJARAN SEBAGAI REFLEKSI KEMANUSIAAN DALAM PRAKTIK PENDIDIKAN - Hisbiyatul Hasanah (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2017)
Learning media in the world of education, the same discussion about humanity itself. Not only because education is a process of forming intellectual and emotional basic skills, but also in education there is a reflection of the human perspective on the relationship between humans and creators, humans with nature, and between humans. Actually, learning is a discussion of interaction and socialization that composes the self-concepts needed from the ability to interpret and support each other's actions. Through education, thus, one increasingly understands its nature as a social human who needs other people, the environment, and even meets God on the journey.